LET dependence of the response of a PTW-60019 microDiamond detector in a 62 MeV proton beam. Issue 9 (September 2016) - Rossomme, S.; Denis, J.M.; Souris, K.; Delor, A.; Bartier, F.; Dumont, D.; Vynckier, S.; Palmans, H.
Highlights: Experimental study of the response of a PTW-60019 microDiamond detector in a proton beam. The study relies on a comparison between the responses of a microDiamond and a chamber. Experimental ion recombination correction applied to the response of the chamber. Good agreement between the responses of both detectors. The microDiamond does not exhibit an LET dependent response in protons. Abstract: This study was initiated following conclusions from earlier experimental work, performed in a low-energy carbon ion beam, indicating a significant LET dependence of the response of a PTW-60019 microDiamond detector. The purpose of this paper is to present a comparison between the response of the same PTW-60019 microDiamond detector and an IBA Roos-type ionization chamber as a function of depth in a 62 MeV proton beam. Even though proton beams are considered as low linear energy transfer (LET) beams, the LET value increases slightly in the Bragg peak region. Contrary to the observations made in the carbon ion beam, in the 62 MeV proton beam good agreement is found between both detectors in both the plateau and the distal edge region. No significant LET dependent response of the PTW-60019 microDiamond detector is observed consistent with other findings for proton beams in the literature, despite this particular detector exhibiting a substantial LET dependence in a carbon ion beam.